(untitled) - Reppen, Randi (Cambridge, 2012)
his package includes the Student's Book, Level 1, and Writing Skills Interactive, Level 1. In the Student's Book, learners study the grammar in a realistic text and through corpus-informed charts and notes. The exercises provide practice in reading, writing, listening, and speaking. Students learn to avoid common mistakes and to apply the grammar in academic writing. Writing Skills Interactive is an online course providing instruction and practice in academic writing skills and academic vocabulary. Animated presentations of the writing skills lead to automatically graded practice. Each unit closes with a quiz, which allows students to assess their progress.
Keywords: Tiếng Anh,English language; Ngữ pháp,Grammar